Whole-body integral dose and post-radiotherapy lymphocytopaenia in solid tumours - Ananya Choudhury; Sanjeeva Gunasekera; Nuradh Joseph; Lanka Alagiyawanna; Thilina Ruwanpura; Lakitha Ruvinda; Sampath Madushan (BMJ Oncology)
Objective Since modern radiotherapy techniques such as intensity-modulated radiotherapy (IMRT) pivot on a strategy of dose redistribution, it may increase integral dose and consequently worsening of lymphocytopaenia. In this study, our objective was twofold: first to validate the correlation between integral body dose and post-treatment lymphocytopaenia in a cohort of patients treated with curative-intent radiotherapy and second to validate its prognostic impact.Methods and analysis Patients treated with curative intent radiotherapy with complete blood counts were included in the study. Data on the following variables were collected: treatment site, prescribed dose, use of concurrent chemotherapy, mean body dose, mean body volume, treatment technique and disease-free survival.Results A total of 116 patients were included for analysis. There was a significant decline in lymphocyte counts after radiotherapy (2.2×109/L vs 0.8×109/L; p<0.001). Multivariate linear regression analysis of post-treatment lymphocytopaenia revealed a significant correlation with pretreatment lymphocyte counts, integral body dose, use of IMRT and use of concurrent radiosensitising chemotherapy. Univariate survival analysis was performed in 37 patients with squamous cell carcinoma of the head and neck. In the Cox proportional hazards model, post-treatment lymphocyte count was statistically significant as a continuous variable (Hazard Ratio=0.998, p=0.01) and as a dichotomous variable.Conclusion The negative correlation between integral body dose and post-treatment lymphocytopaenia was validated, and post-treatment lymphocytopaenia is an adverse prognostic factor in patients with head and neck cancer treated with curative-intent radiotherapy.